2002
DOI: 10.1086/338152
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Immunodeficiency Virus Type 1 Infection on Acute Hepatitis A Virus Infection

Abstract: To assess the possible influence of human immunodeficiency virus type 1 (HIV-1) infection on the clinical course of acute hepatitis A virus (HAV) infection, 15 HIV-1-infected homosexual men and 15 non-HIV-infected age-matched subjects were compared. HAV load was higher in HIV-1-infected than in non-HIV-infected patients (P<.001). Duration of viremia in HIV-1-infected patients (median, 53 days) was significantly (P<.05) longer than in non-HIV-infected patients (median, 22 days). HIV-1-infected patients had lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
3
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 25 publications
3
74
3
3
Order By: Relevance
“…Other studies report viraemic periods varying from 22 up to 490 days [Bower et al, 2000;Kwon et al, 2000;Ida et al, 2002;Costa-Mattioli et al, 2002b;Sagnelli et al, 2003;Normann et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies report viraemic periods varying from 22 up to 490 days [Bower et al, 2000;Kwon et al, 2000;Ida et al, 2002;Costa-Mattioli et al, 2002b;Sagnelli et al, 2003;Normann et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, one would expect immunocompromised persons to have persistent HAV infection. Reportedly, immunocompromised HIVinfected persons are HAV-viraemic for a longer period than expected [Ida et al, 2002;Costa-Mattioli et al, 2002a] and one study found that they show less elevated ALT levels and are longer viraemic than HIV-negative patients [Ida et al, 2002]. Another study found that neonates still excreted HAV 4-5 months after infection [Rosenblum et al, 1991].…”
Section: Discussionmentioning
confidence: 99%
“…64,65 The hepatitis A vaccine became available in 1996, and guidelines recommend for its use among HIV patients with specific risk factors including a history of drug (both injection and non-injection) use, men who have sex with men (MSM), and liver disease including chronic HBV or hepatitis C virus infection. 8 In addition, those traveling to countries endemic for the disease should be vaccinated.…”
Section: Hepatitis a Virusmentioning
confidence: 99%
“…3 Some studies have suggested that acute hepatitis A acts as a possible trigger for the development of autoimmune hepatitis in susceptible individuals: people who exhibit a defect in T lymphocyte suppressors may develop chronic autoimmune hepatitis when exposed to the hepatitis A virus (HAV). 4,5 The virus for acquired immunodeficiency (HIV) can impact on the clinical course of hepatitis A, 6,7 while, on the other hand, HAV-infection may be linked with a prolonged increase in the HIV-viral load. 8,9 Concerned by the existence of this co-infection in our pediatric population, and accepting that the base liver disease (which, in such children, may equally be the consequence of HIV itself, or of opportunistic infections and anti-retroviral therapy) increases the risk of fulminating hepatitis, we decided to investigate the frequency of HAV infection among children exposed to and/or infected by HIV.…”
Section: Introductionmentioning
confidence: 99%